Creating the information basis of spectral masks for automated radiomonitoring - Kipenskiy, A.; Kaliuzhniy, M.; Zadonskiy, O.; Guo, Q. (My University, 2019)
The report presents the results of developing a method for constructing, experimentally checking and creating an information basis for spectral masks for transmitters of basic digital and analog radio technologies. The source data for the construction of spectral masks was a sample of radio electronic devices (RED) types from a database of frequency assignments that differ either by the range of operating frequencies, either by the radiation class, or by the type of modulating data code. A database of spectral masks and an algorithm for their construction was developed on the basis of tabular data. The software product allows the formation of a dynamic list of spectral masks, for visual and convenient work with the developed database (DB) of transmitting devices. His application made it possible to construct spectral masks for transmitting devices of basic digital and analog radio technologies. For integration into the spectrum analyzers, the possibility of mass translation of table values into the necessary formats is provided.
Keywords: infocommunication facilities; database.; radio electronic devices; spectral masks; automated radiomonitoring